Effect of plant growth-promoting rhizobacteria on the growth and yield of jalapeño pepper - Camacho-Rodríguez, María; Almaraz-Suárez, Juan José; Vázquez-Vázquez, Cirilo; Angulo-Castro, Azareel; Ríos-Vega, María Esther; González-Mancilla, Apolinar (Revista Mexicana de Ciencias Agrícolas, 2022)
Jalapeño pepper is one of the most cultivated plants, its production has decreased due to the low fertility of the soil and the presence of diseases. Plant growth-promoting rhizobacteria are alternatives to improve the growth and yield of this crop. The objective was to evaluate the effect of rhizobacteria (Serratia marcescens, S. plymuthica, S. liquefaciens and Arthrobacter sp.) on the growth of jalapeño pepper. The experiment was established in 2020, in Gómez Palacio, Durango, Mexico. The effect of rhizobacteria was tested at the in vitro, seedbed and pot level, completely randomly designed with 15 and 8 repetitions. The variables evaluated were height, number of leaves, leaf area, chlorophyll content index, dry biomass in root, leaves and stems, number and size of fruits. The treatments evaluated were absolute control, fertilized control and the four rhizobacteria. The substrate used was a mixture prepared based on peat moss (Premier®), perlite (Agrolita®) and vermiculite (Agrolita®) with a ratio of 1:1:1 (w/w/w), the soil had a pH of 8.3, 2.2% of organic matter, 61.5 mg kg-1 of nitrogen (NO3) and 20.2 mg kg-1 of phosphorus. The rhizobacterium S. plymuthica allowed greater height and leaves in seedlings (in vitro and seedbed), but under pot conditions, S. marcescens showed better height, number of leaves, leaf area and plant biomass, S. plymuthica increased the amount of chlorophyll, and finally S. liquefaciens increased the number and size of fruits. Rhizobacteria can improve the growth and yield of jalapeño pepper.
Keywords: Arthrobacter sp.; Capsicum annuum L.; Serratia liquefaciens; Serratia marcescens; Serratia plymuthica